-38=6(v-5)-8v

Simple and best practice solution for -38=6(v-5)-8v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -38=6(v-5)-8v equation:



-38=6(v-5)-8v
We move all terms to the left:
-38-(6(v-5)-8v)=0
We calculate terms in parentheses: -(6(v-5)-8v), so:
6(v-5)-8v
We add all the numbers together, and all the variables
-8v+6(v-5)
We multiply parentheses
-8v+6v-30
We add all the numbers together, and all the variables
-2v-30
Back to the equation:
-(-2v-30)
We get rid of parentheses
2v+30-38=0
We add all the numbers together, and all the variables
2v-8=0
We move all terms containing v to the left, all other terms to the right
2v=8
v=8/2
v=4

See similar equations:

| 10z-16-100-3z=24 | | 2z+23=1/2 | | -1/6t=-15 | | 2z+23=1÷2 | | 3x^2+15x-85=0 | | 2x+1x+1=7/4 | | 12y+42=10y+7 | | 7a+25=15+9a | | 5(3x+1)-10=25 | | 10x-3=11x-4 | | 5+16w=6w=45 | | Z^2+2x=3 | | y=2(-3) | | 4/35=x/100 | | 27y=-9 | | 6+3y=-y | | 12x-198=4x-6 | | 1.49=5/x | | 2x+-6=8x+4 | | 8x^2-19x+32=0 | | 6x-13=9x+6 | | 2^x+32x=0 | | x3+x2+14=0 | | (3x)7=40 | | 3x-5–5x=3 | | 4x^2-32=2x^2 | | 8g²-6g-5=0 | | (9)2x=729 | | 9^2x=729 | | x=11+8x=20 | | 3x/7-x+1/14=2 | | 8x+44=4(x+2) |

Equations solver categories